Gartland type III supracondylar fracture in children: is open reduction really a dangerous choice?. (March 2022) - Tarallo, Luigi; Novi, Michele; Porcellini, Giusepe; Schenetti, Cecilia; Micheloni, Gian Mario; Maniscalco, Pietro; Catani, Fabio
Highlights: Complicated supracondylar fractures type III in children cannot be management always with closed reduction. Open reduction and percutaneous pinning should be considered an effective treatment for type III supracondylar fracture with complex injury associated. Open reduction and internal fixation have not showed more complications than closed reduction Abstract: Background: Type III supracondylar fractures represent a difficult injury to treat and there is no universal consensus regarding the best treatment. The purpose of this study is to assess the incidence of complication associated with open reduction and compare open reduction vs closed reduction, in order to determine which treatment lead to better clinical and radiological outcomes. Is open reduction really associated with a higher number of iatrogenic complication and worse clinical outcomes in comparison to closed reduction? Methods: A total of 55 patients, affected by type III supracondylar humerus fracture, were retrospectively selected and divided into two groups according to which type of treatment they received (open reduction or closed reduction). Major complications correlated with surgical procedure, such as infections, neurovascular iatrogenic lesions, elbow stiffness and painful scarring were assessed. The treatment outcomes and clinical features were compared among the two groups. A statistical analysis to find association between the type of reduction, the restored elbow anatomy and the clinical outcomes were performed. The follow-up varies between 1 year and 7 years. Results: No major complications occurred in our series of patients. Excellent and good outcomes were reported among all 26 patients that underwent an open reduction surgery and in 23 out of the 29 patients who received a closed reduction surgery. A higher number of patients in the open reduction group presented angles with normal values; moreover 3 out of the 6 patients with unsatisfactory outcomes presented with angles not in range, underlying the presence of a connection between the restored elbow anatomy and the clinical outcomes. There were no differences among the two groups regarding the presence of complications. Discussion: Open reduction should not be considered as a first line option of treatment in any pediatric patient with a type III supracondylar humerus fracture, but in several cases open surgery must be viewed as the choice with the best outcomes not only in presence of neurovascular lesion but also in case of irreducible fracture.